Evolução cultural em análogos experimentais de metacontingências: seleção de diferentes produtos agregados - Gadelha, Claudia Teixeira (2010)
Human behavior is accounted by three levels of variations and selection: filogeny, ontogeny and cultural. Metacontingency is a concept that deals with cultural level phenomena. It postules, in analogy with operant behavior, that interlocking behavioral contingencies and their aggregate product are selected by its consequences. This research has been driven by the following inquiry: Will IBCs and aggregate products of different inicial probability be selected by differential magnitudes of cultural consequences?. In a multiple trials procedure, two undergraduate students would work together, on a computer task (even though each one worked on a different computer) and could interact freely. When the stability criteria was attained, one of the participants would be replaced by another. In each trial, 4 numbers would appear on each computer screen. The participants task consisted in typing in another 4 numbers. When all the sums of both numbers (given by the computer and typed by the participant) resulted in odd numbers, points were earned by the participant. During the trials, the sum of the numbers typed in by the participant would appear in a box. Different relations between the sum of the numbers typed in by each participant would lead to different consequences. Contingencies less and less probable would lead to bigger and bigger magnitude of consequences. Therefore, when: a) the sum of the numbers typed in by one participant was bigger than the sum of the other, each participant would earn 100 bonus; b) the sum of the numbers typed in by one participant was twice as large as the sum of the other participant, then each would earn 200 bonus; and c) the sum of the numbers typed in by one participant was equivalent to the other one s squared, then each would earn 300 bonus. The first experiment was composed of 14 generations. Two non-naïve participants were brought into the experimental session to make sure that all three aggregate products would occur. All three types of aggregate products were selected, one after the other. The second experiment was composed of an all-naïve 22 generations. The two first aggregate products were selected simultaneously, after 7 generations. However, variations in the main aggregate product proceded in the following generations. The results of both experiments indicated selections of/throughout metacontingencies